Alpha-1-antitrypsin deficiency: increasing awareness and improving diagnosis. (February 2016) - Greulich, Timm; Vogelmeier, Claus F.
Alpha-1-antitrypsin deficiency (AATD) is a hereditary disorder that is characterized by a low serum level of alpha-1-antitrypsin (AAT). The loss of anti-inflammatory and antiproteolytic functions, together with pro-inflammatory effects of polymerized AAT contribute to protein degradation and increased inflammation resulting in an increased risk of developing chronic obstructive pulmonary disease (COPD) and emphysema, especially in smokers. AATD is a rare disease that is significantly underdiagnosed. According to recent data that are based on extrapolations, in many countries only 5–15% of homozygous individuals have been identified. Furthermore, the diagnostic delay typically exceeds 5 years, resulting in an average age at diagnosis of about 45 years. Although the American Thoracic Society/European Respiratory Society recommendations state that all symptomatic adults with persistent airway obstruction should be screened, these recommendations are not being followed. Potential reasons for that include missing knowledge about the disease and the appropriate tests, and the low awareness of physicians with regard to the disorder. Once the decision to initiate testing has been made, a screening test (AAT serum level or other) should be performed. Further diagnostic evaluation is based on the following techniques: polymerase chain reaction (PCR) for frequent and clinically important mutations, isoelectric focusing (IEF) with or without immunoblotting, and sequencing of the gene locus coding for AAT. Various diagnostic algorithms have been published for AATD detection (severe deficiency or carrier status). Modern laboratory approaches like the use of serum separator cards, a lateral flow assay to detect the Z-protein, and a broader availability of next-generation sequencing are recent advances, likely to alter existing algorithms.